Ground improvement using waste shell for farm roads and embankments - Siti Hanggita Rachmawati; Zakaria Hossain; Jim Shiau (Journal of Agricultural Engineering, 2018)
The bearing capacity of subgrade soil plays an important role in the performance of agricultural earth structures such as farm roads or earth embankments. It also has a strong link to the budgeting efficiency of those agricultural earth structural projects. One way to improve the subgrade of soil is by using stabilised material in the subgrade layer. Shell husk waste is one of the construction materials that can be used as a substitute for the subgrade layer. The utilisation of shell husk waste has several purposes such as protecting natural aggregate and preventing problems that arise from the untreated abandoned shell husk waste. In this research, shell husk waste was used as farm road subgrade material. To understand the bearing capacity of soil specimens, a series of California bearing ratio (CBR) tests were carried out by using several types of subgrade layers containing different percentages of shell husk in the soil-shell husk mixture. Three types of subgrade layers were used: subgrade upper layer, subgrade bottom layer, and subgrade double layer, containing 0 (control), 10, 20, and 30% shell husk in soil-shell husk mixture. The experimental results showed that the addition of shell husk in soil leads to improvement in the CBR values of the ground as compared to control specimens. It was further revealed that by increasing the percentage of shell husk in the soil-shell husk mixture, the CBR value was improved significantly. The highest CBR value was achieved by using subgrade upper layer with a 30% shell husk in soil-shell husk mixture. The results obtained are encouraging with regard to the utilisation of the waste shell husks for improving the bearing capacity of agricultural earth structures such as farm roads and earth embankments.